2021
DOI: 10.3390/ijms22095018
|View full text |Cite
|
Sign up to set email alerts
|

Proteases, Mucus, and Mucosal Immunity in Chronic Lung Disease

Abstract: Dysregulated protease activity has long been implicated in the pathogenesis of chronic lung diseases and especially in conditions that display mucus obstruction, such as chronic obstructive pulmonary disease, cystic fibrosis, and non-cystic fibrosis bronchiectasis. However, our appreciation of the roles of proteases in various aspects of such diseases continues to grow. Patients with muco-obstructive lung disease experience progressive spirals of inflammation, mucostasis, airway infection and lung function dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 213 publications
(228 reference statements)
1
11
0
1
Order By: Relevance
“…This highlights the importance of CAP1 for ENaC regulation in the lung in situations associated with liquid accumulation in the alveolar region. This finding is in agreement with in vitro studies that found that proper ENaC function in the lung relies on the activity of multiple proteases and not just CAP1 [ 38 , 44 ]. Nevertheless, the understanding of how certain proteases regulate ENaC function in vivo remains mysterious, as indicated by the study of Donaldson and colleagues [ 41 ].…”
Section: Enac Regulation By Proteasessupporting
confidence: 92%
“…This highlights the importance of CAP1 for ENaC regulation in the lung in situations associated with liquid accumulation in the alveolar region. This finding is in agreement with in vitro studies that found that proper ENaC function in the lung relies on the activity of multiple proteases and not just CAP1 [ 38 , 44 ]. Nevertheless, the understanding of how certain proteases regulate ENaC function in vivo remains mysterious, as indicated by the study of Donaldson and colleagues [ 41 ].…”
Section: Enac Regulation By Proteasessupporting
confidence: 92%
“…Under the direction of these chemotactic mediators, neutrophils migrate into the respiratory tract and secrete serine proteases, including neutrophil elastase, cathepsin G, and proteinase-3, which damage tissues and stimulate mucus secretion from submucosal glands and goblet cells. Neutrophils also secrete matrix metalloproteinase (MMP)-8 and MMP-9, which contribute to alveolar destruction and development of emphysema [15,43,44].…”
Section: Oxidative Stress In the Development And Progression Of Copdmentioning
confidence: 99%
“…Furthermore, KIRA8 strongly induced the secretion of serine protease inhibitors. Proteases and protease inhibitors in the normal lungs coordinate their functions in lung injury and repair [ 57 , 58 ]. Dysregulation of the proteases–antiproteases balance is crucial in the manifestation of different types of lung diseases, such as chronic obstructive pulmonary disease (COPD), asthma, cystic fibrosis, and acute respiratory distress syndrome, where a marked increase in protease activities was observed [ 59 , 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%